2013
DOI: 10.1371/journal.ppat.1003599
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Autophagy Contributes to Measles Virus Infectivity

Abstract: The interplay between autophagy and intracellular pathogens is intricate as autophagy is an essential cellular response to fight against infections, whereas numerous microbes have developed strategies to escape this process or even exploit it to their own benefit. The fine tuned timing and/or selective molecular pathways involved in the induction of autophagy upon infections could be the cornerstone allowing cells to either control intracellular pathogens, or be invaded by them. We report here that measles vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
156
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(166 citation statements)
references
References 45 publications
(66 reference statements)
10
156
0
Order By: Relevance
“…One recent observation is that the expression of MeV-C is required for the induction of late autophagy in infected HeLa cells, subsequent to MeV replication [16]. In the present study, we found that PPRV-C significantly increased the level of LC3-II and promoted the degradation of p62.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…One recent observation is that the expression of MeV-C is required for the induction of late autophagy in infected HeLa cells, subsequent to MeV replication [16]. In the present study, we found that PPRV-C significantly increased the level of LC3-II and promoted the degradation of p62.…”
Section: Discussionsupporting
confidence: 70%
“…In recent years, an increasing number of studies have demonstrated that the infection processes of morbilliviruses are closely related with autophagic flux [16,17]. However, the coxsackievirus B3, herpes simplex virus and influenza A virus have been shown to induce autophagosome formation but block the fusion of autophagosomes with lysosomes [4850].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations